Effect of Fermentation Time, Moisture Content, and Temperature on Sorbitol Production Via Solid State Fermentation Process - Zuriana Sidi, Ahmad; Mimi Sakinah, A. M. (Universiti Malaysia Pahang, 2017)
Malaysia is the largest country that has produced many types of waste. One of it is Meranti wood sawdust. These wastes result in a significant environmental problem if not dispose it in the proper manner. The main objective of this article is to produce the high yield of sorbitol by solid state Fermentation (SSF) process from pretreated Meranti wood sawdust using bacterium Lactobacillus plantarum (BAA 793; NCIMB 8826). One factor at a time (OFAT) was studied for further process using solid state fermentation (SSF) process and investigated the effect of relevant parameters (fermentation time, range: 2 hours to14 hours, moisture content, range: 40% to 90%, temperature, range: 25oC to 45oC) to the solid-state fermentation (SSF) process in producing high yield of sorbitol. The highest product yield was obtained at 50% moisture content, at 10 hours of fermentation time and 35oC of incubation temperature where the concentration of sorbitol was 25.68 g/L respectively. This study also showed that the solid state fermentation (SSF) process will produce the high yield of sorbitol production compared to the submerged fermentation and could serve as a-low cost substrate for bioproducts production especially sorbitol.